STUDENTSâ PERCEPTION OF THE USE EVERNOTE APPLICATION ON BASIC ENGLISH WRITING SKILLS IN JUNIOR HIGH SCHOOL - M. Firza Novriansyah; Ernita Daulay (Indonesian EFL Journal)
This research aims to analyze students' writing skills using the Evernote application. This research uses a qualitative research design, the participants are junior high school students in Medan. Data was obtained from questionnaires and interviews. This research focuses on junior high school students in Medan. A total of 10 students became participants in this research and 3 students were selected to answer interview questions. The data collection technique used in this research is a non-test technique which comes from two sources, namely questionnaires and in-depth interviews. The results show that 60% of students agree that the Evernote application can help their writing abilities. As many as 80% of students agree that Evernote provides complete and easy to understand information. As many as 70% of students felt very satisfied, and as many as 70% thought Evernote was an effective learning medium to help their English writing skills. Overall, students responded positively to using Evernote to help improve their writing skills. In addition, the Evernote application provides various interesting and easy-to-use features that can help language development. Overall, this study contributes to the existing literature on technology-enhanced language learning by providing insight into how middle school students use Evernote for basic English writing.Keywords: development; evernote application; studentsâ perception; writing abilityÂ